Design of Smart Home Pharmacy - Drabee, Bayan; Sbeih, Fatima (جامعة بوليتكنك فلسطين - اجهزة طبية, 2017)
يحتاج المرضي المسنون إلى رعاية خاصه. وعاده ما تاخذ عده أنواع من الادويه في أوقات مختلفه. وهذا يتطلب مساعده من الناس الأصحاء لأولئك الذين تتراوح أعمارهم بين المرضي للحفاظ علي الادويه في مكان أمن ، وإعطاء كل دواء في الوقت المناسب. فكره هذا المشروع هي لتصميم الصيدلة الذكية التي يمكن ان توفر للمرضي الذين تتراوح أعمارهم بين جميع المرافق التي يمكن ان تساعدهم دون اي حاجه من الناس الأصحاء. منذ الحرارة ، والهواء ، والضوء ، والرطوبة قد تضر الدواء ، والصيدلة الذكية تتكون من غرف للحفاظ علي الادويه من الهواء ، وأجهزه الاستشعار التي تقيس درجه الحرارة ، والرطوبة من الغرف ، لتخزين الدواء بشكل صحيح والحفاظ عليه من الحصول علي تلف ظروف التخزين عن طريق قياس درجه الحرارة والرطوبة ، وتفعيل المروحة تلقائيا عندما تكون خارج النطاق. يمكن للمستخدم تحديد عدد المرات في اليوم الجرعة ينبغي ان تؤخذ والوقت لكل جرعه وفقا للطبيب وصفه طبية, ثم يرسل النظام رسالة sms إلى الهاتف المحمول للمريض لتذكيره باتخاذ كل المخدرات في الوقت المحدد. وعلاوة علي ذلك ، فان النظام يعطي المستخدم اشاره إلى القطع المتبقية من المخدرات في كل غرفه وتاريخ انتهاء صلاحيتها لكل منها. المشكلة الرئيسية التي تواجه المرضي وخاصه الذين تتراوح أعمارهم بين واحد اتخاذ الادويه التي يمكن ان تسبب النسيان المرضي الذين تتراوح أعمارهم بين. هذا المشروع في هذه الاطروحه هو حول الدوائر الخاضعة للرقابة التي تهدف إلى تنظيم الوقت من تستمر عبر استخدام تقنيه خاصه ، مثل محركات ، وحده تحكم مايكرو ، وجميع من العنصر الكتروني للمرضي الذين يحتاجون إلى العديد من تستمر. Aged patients needs special care. Usually they take several types of medicines in different times. This requires help from healthy people to those aged patients to keep the medicines in safe place, and give each medicine in time. The idea of this project is to design smart pharmacy that can provides the aged patients with all the facilities that can help them without any need from healthy people. Since heat, air, light, and moisture may damage the medicine, the smart pharmacy consists of chambers to keep medicines from air, and sensors that measure the temperature, and humidity of the chambers, to store the medicine properly and keep it from getting damaged.storage conditions by measuring its temperature and humidity, and automatically activating the fan when they are out of range.The user can specified the number of times per day the dose should be taken and the time for each dose according to the doctor prescription, then the system sends sms message to patient's mobile phone to remind him to take each drug in the specified time. Furthermore, the system gives the user an indication of the remaining drug pieces in each chamber and the expired date for each. The main problem which faces the patients especially the aged one taking numerousness medicines which may cause oblivion to the aged patients. This project in this thesis is about controlled circuit that designed to organize the time of drags via using special technique ,such as engines, micro controller ,and all of the electronic element to the patients who need many drags.
CD, no of pages56 , 30307, اجهزة طبية2/2017, in the store
Keywords: Smart ,Home, Pharmacy